Further thoughts on the syntax of Il. 5.265-269 - Willi, A (Brill Academic Publishers, 2017)
In response to a recent article by P. Probert on the same passage, it is argued that we need not assume that Il. 5.265–269 obliquely refers to an otherwise unknown ‘stud farm’ of Zeus if we want to maintain that the phenomenon of attractio relativi is only attested in post-Homeric times. The relative pronoun ἧς on which Probert’s reading is based should rather be understood as representing either a ‘descriptive’ genitive or, even more likely, an early instance of the genitive of price.